Spirituality and Social Cultural Education Factors in Instilling an Entrepreneurial Spirit Miftahul Ulum Teluk Bakong Education, West Kalimantan - Hukma Fikria (al-Afkar, Journal For Islamic Studies, 2023)
Education is one of the driving factors in developing students' abilities in the realm of entrepreneurship. This study aims to discuss the Spirituality and Social Cultural Education Factors in Instilling an Entrepreneurial Spirit in the Education of Miftahul Ulum Teluk Bakong, West Kalimantan, to see the influence resulting from spiritual and social cultural education to become a pattern of student development. This research is included in the qualitative cluster with the nature of literature studies that examines problems with sources that have been written in advance by researchers and matched with field observations so that they become complete texts between reality and facts and are focused on library research. The data used comes from previous literature and field observations. This is done by the author to see the dynamics of education in forming entrepreneurial skills. Data analysis uses data reduction, data display and draws conclusions. In other words, that in this study the authors used several references and reference materials that have relevance to the title raised in this study. The results of this study Spiritual education, as well as social attitudes have a role in having factors that shape entrepreneurial attitudes. Where spiritual factors play a role in shaping spiritual attitudes, there are several things to develop spiritual values ​​and awareness which include life goals, ethics, integrity, empathy, gratitude, and perseverance. One of Miftahul Ulum's education programs has instilled spiritual values ​​to create students who are able to compete in the outside world regarding the economy. These factors can influence the attitude of an entrepreneur in doing business, such as long-term orientation, holistic thinking, and a sense of social responsibility.